Changing characteristics of cancer patients during the COVID-19 pandemic - Korkusuz, Ramazan; Sahingoz Erdal, Gulcin; Kibar Akilli, Isil; Bilge, Müge; Tural, Deniz; Kart Yasar, Kadriye (The Journal of Infection in Developing Countries, 2022)
Introduction: Cancer patients are more sensitive to infections, and, compared to other patients, may have more serious outcomes. Thus, cancer patients are a high-risk group in the COVID-19 pandemic. The aim of this study was to evaluate how cancer patients are affected by COVID-19 infection; the prevalence, and factors affecting mortality. Methodology: This single-centre, retrospective study included cancer patients under follow-up treatment at our hospital with a laboratory-confirmed diagnosis of COVID-19. Demographic and clinical data were obtained from electronic medical records. The effects of tumour subtype and patient demographic data on COVID-19 prevalence and mortality were analyzed using univariate and multivariate models. Results: Evaluation was made of 217 cancer patients, comprising140 (64.5%) males and 77 (35.5%) females with a mean age of 62.05 ± 12.95 years. Mortality was seen in 84 (38.7%) patients. Disease grade, chemotherapy within the last 3 months and CT findings were determined to be related to mortality. In logistic regression analysis, the most important factors affecting survival were determined to be severe lung involvement (p < 0.001) and hematological malignancy. Conclusions: It is clear that cancer patients are at greater risk from COVID-19 infection than individuals without a malignant disease. The results showed that cancer patients with different tumour types had different levels of sensitivity to COVID-19. It is clear that with ongoing viral mutations, the duration of the pandemic is unknown. Therefore, the continuation of cancer screening and cancer treatments should not be interrupted.